2019
DOI: 10.1016/j.euf.2018.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Haematuria in Sport: A Review

Abstract: Blood in the urine following exercise is a common phenomenon and occurs due to vascular responses to sports and trauma as well as blood and muscle cell breakdown. Although it may not be present in all cases of trauma, blood in the urine should be investigated due to the risk of discovering underlying injury to the urinary tract and other incidental findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 33 publications
0
14
0
4
Order By: Relevance
“…The increased risk of ID and iron deficiency anemia in athletes is thought to be due to factors, such as foot-strike induced hemolysis, insufficient dietary intake, increased iron losses, and suppressed intestinal iron absorption caused by inflammation [19][20][21][22]. Ferritin is the cellular storage protein for iron, and circulating levels are generally considered reflective of total body iron stores [23].…”
Section: Introductionmentioning
confidence: 99%
“…The increased risk of ID and iron deficiency anemia in athletes is thought to be due to factors, such as foot-strike induced hemolysis, insufficient dietary intake, increased iron losses, and suppressed intestinal iron absorption caused by inflammation [19][20][21][22]. Ferritin is the cellular storage protein for iron, and circulating levels are generally considered reflective of total body iron stores [23].…”
Section: Introductionmentioning
confidence: 99%
“…The potential mechanisms of renal injury, demonstrated by hematuria, leukocyturia, and creatinine levels are tract trauma, hypoxic renal injury and ischemia, release of a hemolysing factor during exercise, dehydration, products of hemolysis, myoglobinuria release, and peroxidation of red blood cells (Bellinghieri et al., 2008; Akiboye and Sharma, 2018). In our study, we also observed a higher percentage of runners with impairment of hemolysis metabolites and myoglobinuria with the RR genotype compared to those with the XX genotype.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we also observed a higher percentage of runners with impairment of hemolysis metabolites and myoglobinuria with the RR genotype compared to those with the XX genotype. Hematuria also could be attributed to bladder trauma, foot strike, presence of dysmorphic red blood cells, acidosis, and hypoxia-related glomerular injury (Bellinghieri et al., 2008; Shephard, 2016; Grygorczyk and Orlov, 2017; Akiboye and Sharma, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The more trauma involved in the exercise, the greater the risk of haematuria, but even non‐contact athletes such as rowers, can have the same problem. It is not found in sedentary stressful activities such as taking exams . When such a cause of NVH is suspected, retesting the urine at least 48 hours after exercise is appropriate.…”
Section: How Was the Haematuria Found?mentioning
confidence: 99%